Stochastic schemes for the perturbation of the atmospheric boundary conditions in ocean general circulation models - Storto, Andrea; Yang, Chunxue (Frontiers in Marine Science, 2023)
Advancing the representation of uncertainties in ocean general circulation numerical models is required for several applications, ranging from data assimilation to climate monitoring and extended-range prediction systems. The atmospheric forcing represents one of the main uncertainty sources in numerical ocean models. Here, we formulate and revise different approaches to perturb the air-sea fluxes used within the atmospheric boundary conditions. In particular, perturbation of the fluxes is performed either through i) stochastic modulation of the air-sea transfer coefficients; ii) stochastic modulation of the air-sea flux tendencies; iii) coarse-graining of stochastic sub-grid computation of the fluxes; or iv) multiple bulk formulas. The schemes are implemented and tested in the NEMO4 ocean model, implemented at an eddy-permitting resolution on a domain covering the North Atlantic and Arctic oceans and the Mediterranean Sea. A series of 22-year 4-member ensemble experiments with different stochastic schemes are performed and analyzed for the period 2000-2021, and results are compared in terms of the ensemble mean and, when applicable, ensemble spread of the principal oceanic diagnostics. Results indicate that the schemes, in general, can significantly improve some verification skill scores (e.g. against drifter current speed, SST analyses, and hydrographic profiles) and, in some cases, enhance the mesoscale activity and weaken the large-scale circulation. The response, however, is different depending on the specific scheme, whose choice thus depends on the target application, as detailed in the paper. These findings foster the adoption of these schemes in both extended-range operational ocean forecasts and coupled long-range climate prediction systems, where the boundary conditions perturbations may contribute to performance increases.